Isolation and molecular identification of halotolerant diazotrophic bacteria from The Northern Coastal of Pemalang, Central Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Purwanto, Oktaviani E, Leana NWA. 2022. Isolation and molecular identification of halotolerant diazotrophic bacteria from The Northern Coastal of Pemalang, Central Java, Indonesia. Biodiversitas 23: 5814-5821. Plant Growth Promoting Bacteria can fix nitrogen, a very important macronutrient for plant growth. However, the application of urea as a source of this macronutrient has a negative impact on the environment. Therefore, developing biofertilizers using N-fixing bacteria is an environmentally friendly technology. Therefore, this research aimed to isolate and analyze the diversity of N2-fixing bacteria from saline rice fields. The soil samples were taken from the rhizosphere of rice plants in Nyamplung Sari Village, Petarukan District, Pemalang Regency. Meanwhile, 9 (nine) isolates of nitrogen-fixing bacteria have been isolated, which can fix N2. The isolates can bind to N2, but only a few can produce IAA. The nitrogen-fixing ability of diazotrophic bacteria ranged from 17.85 ppm to 29.05 ppm. Isolate Jn3 has the highest ability to fix nitrogen, reaching 29.05 ppm, while Jn3, J, J12, J5, Kn1, and A3 can produce IAA with values of 2.00, 2.69, 2.22, 1.76, 3.47, and 1.79 ppm, respectively. Based on the 16S rRNA analysis and phylogeny construction, the isolated bacteria were identified in 3 (three) clusters. The first cluster was identified as Pseudomonas stutzeri and Acinetobacter junii (Kn1 and Jn3), while the second was identified as Bacillus cereus, Bacillus tropicus, Bacillus altitudinis, and Bacillus subtilis (Jn, Jn1, A3, and K3 isolates). The third cluster was identified as Bacillus pumilus, Acinetobacter baumanii, and Acinetobacter schindleri (J12, J5, and J). In addition, our study reported the findings of Acinetobacter baumannii and Acinetobacter schindleri species that can fix nitrogen.
Keywords: Bacteria, diazotroph, halotolerant, N2, saline